A new species of Trisecodes from the Afrotropics (Hymenoptera, Eulophidae) - Gumovsky, Alex (Zootaxa, 2014)
The first Afrotropical species of Trisecodes Delvare & LaSalle, 2000, T. africanum Gumovsky, sp. n., is described from localities in Uganda, Guinea and Cameroon. The new species differs from the type species of the genus, T. agromyzae, which was described from the Neotropical region in Belize, mostly by having longitudinally strigate sculpture on the mesosoma dorsally and by the fore wing being somewhat darkened in its basal three-fifths. A possible Gondwanan origin of the genus is postulated.